Performance of lentil (Lens culinaris) and toria (Brassica campestris) intercropping with wheat (Triticum aestivum) under rainfed conditions of north-west Himalaya - TUTI, M D; MAHANTA, D; MINA, B L; BHATTACHARYYA, R; BISHT, J K; BHATT, J C (The Indian Journal of Agricultural Sciences, 2012)
A field experiment was conducted during winter (rabi) seasons of 2008–09 and 2009–10 at Hawalbagh to evaluate the performance of lentil (Lens culinaris Medikus) and toria (Brassica campestris L. var. toria) intercropping with wheat (Triticum aestivum L. emend. Fiori & Paol.). Wheat + lentil in 2:1 and 1:1 row ratios were superior to sole wheat and wheat + toria intercropping. Lentil yield was higher in 1:1 (0.45 tonne/ha) than in 2:1 (0.31 tonne/ha). Similarly, toria recorded higher yield in 1:1 (0.41 tonne/ha) than in 2:1 (0.30 tonne/ha) ratio. The highest wheat-equivalent yield (5.24 tonnes/ha), net returns (Rs 36 770/ha), benefit: cost ratio (1.81), monetary advantage index (Rs 7 207) and land-equivalent ratio (1.19) were obtained with wheat + lentil under 2:1 row ratio followed by 1:1 ratio. Negative values of aggressivity under intercrop indicated that wheat was dominant, and lentil and toria were the dominated crops. Competitive ratio and relative crowding coefficient of wheat was higher under intercropping of wheat with lentil under 1:1 and 2:1 ratios, respectively. Relative crowding coefficient of the system was highest for wheat + lentil under 2:1 ratio intercropping (5.90). Similarly, water use efficiency (27.6 kg/ha-mm) was highest with wheat + lentil under 2:1 ratio.